REPRESENTASI DISKRIMINASI ETNIS TIONGHOA DALAM FILM BABI BUTA YANG INGIN TERBANG - Rio Febriannur Rachman (Kanal: Jurnal Ilmu Komunikasi, 2014)
This study focuses on the discrimination toward Chinese-Indonesian before the reformation era represented on Babi Buta yang Ingin Terbang (Blind Pigs Who Want to Fly) movie. This study aims to elaborate the types and effects of discrimination which occur toward Chinese-Indonesian based on that movie. It uses qualitative method. Interpretation about social codes based on semiotics is used to strengthen this study. Every scene of the movie which represents discrimination is explained descriptively. The result, there are four main point of types and effects discrimination toward Chinese-Indonesian: labeled as ‘the other’, having low self-esteem, being violence victim, and intimidated from every side.